Grafting Of Maleic Anhydride onto Cyclized Natural Rubber In The Melt Phase: The Effect of Maleic Anhydride Consentrations on the Spesific Weight and Total Acid - M. Said Siregar; Desi Ardilla; Asmara Sari Nasution (Proceeding International Seminar of Islamic Studies, 2019)
The grafting product of maleic anhydride onto cyclized natural rubber have been produced which is processed in an internal mixer 150oC 80 rpm. In this research, the consentrations of maleic anhydride used is 2, 4, 8, 16 phr. All grafted product was purified to determine the spesific weight and total acid for each graft product by the titration method. Specific weights of grafting products by addition of AM 2,4,8,16 is 0.245, 0.276, 0.288, 0.304, and total acid is 3.272, 6.145, 6.145, 10.280 respectively.